AB0907 The prevalence of vertebral fractures and their relationship with bone mineral density in mild ankylosing spondylitis men pacients. (23rd January 2014) - Stoica, S.; Zugravu, G.
Abstract : Background: Osteoporosis (OP) is a frequent complication of ankylosing spondylitis (AS), even in early stages of the disease. Objectives: Dual x-ray absorptiometry for assessing bone mineral density (BMD) has limitations in patients with AS because of unreliability of spinal measurements, particularly in advanced disease with new bone formation.The objective is to determine bone mineral density (BMD) in men patients with mild ankylosing spondylitis (AS), to establish the prevalence of vertebral fractures and fracture risk in these patients, and to determine the relationship between BMD and vertebral fractures. Methods: 34 men aged 40-60 years with mild AS were studied. BMD of the lumbar spine and femoral neck was measured by dual X-ray absorptiometry (DXA) and radiographs of the thoracic and lumbar spine were obtained in all subjects. From the radiographs, vertebral fractures were characterized by a morphometric technique using established criteria. 39 healthy male subjects aged 50–60 years, recruited from primary care registers, had spinal radiographs performed and served as controls for vertebral fractures. Results: In patients with AS, BMD was reduced in both the lumbar spine 0.97 (0.1) g/cm 2 [ T score -1.10 (1.3), 95% confidence interval (CI) -0.50, +0.14] and femoral neck 0.82 (0.1) g/cm 2 [ T score -1.40 (1.2), 95% CI -0.51, +0.09]. 6 pacients of 34 (17, 6%) patients with AS had a vertebral fracture, compared with 1 of 39 (2, 6%) controls; odds ratio 5.92 (95% CI 1.4, 23.8). AS patients with fractures were not significantly older (mean age 41.4 vs 37.8 yr, P =0.17), but had significantly longer disease duration (12.4 vs 9.3 yr, P <0.05) than patients without fractures. No significant difference was found in the visual analogue scores for pain in AS patients with fractures compared with those without. No significant correlation was observed between BMD of the lumbar spine or femoral neck and vertebral fractures in patients with AS. In addition, there was no significant difference in the lumbar spine or femoral neck BMD in AS patients with fractures compared with those without. Conclusions: Spinal and hip osteopenia and vertebral fractures are a feature of mild AS. However, there was no correlation between BMD and vertebral fractures in these patients. AS patients with mild disease had a higher risk of fractures compared with the normal population and this increased with the duration of disease. References: Wendling D. Bone loss in ankylosing spondylitis: Can we put the puzzle together? J Rheumatol 2005, 32: 1184-1186. Toussirot E, Wendling D. Bone mass in ankylosing spondylitis, Clin Exp Rheumatol 2000, 18 (Suppl 21):S16-S20. Jergas M, Uffman M, Escher H et al. Interobserver variation in the detection of osteopenia by radiography and comparison with dual x-ray absorptiometry (DXA) of the lumbar spine, Skeletal Radiol 1994, 23: 195-199 Genant H, Engelke K, Fuerst T et al. Noninvasive assessment of bone mineral and structure: state of art, J Bone Miner Res 1996, 11: 707-730 Will R, Bhalla AK, Palmer R et al. Osteoporosis in early ankylosing spondylitis: a primary pathological event? Lancet 1989, 2: 1483–1485 Disclosure of Interest: None Declared